OPTIMALISASI METODE PEMBELAJARAN PADA MASA TRANSISI MENUJU PEMBELAJARAN HYBRID - Siti Maesaroh; Dhea Adela (STKIP Subang, 2022)
The purpose of this research is to describe how to optimize learning methods during the transition period towards hybrid learning so that understanding of the material is conveyed to students. This type of research uses a qualitative descriptive method. Data collected through observation, interviews and documentation. Test the validity of the data using triangulation techniques. The results of this study indicate that it is true to use hybrid learning as a solution in achieving student material towards an endemic transition. Thus, the learning method used in the implementation of learning at that time can be said to be effective because the learning objectives are achieved. This achievement is the result of hybrid learning where the teacher can convey material directly and obtain satisfactory learning outcomes.